Advances in CAR-NK cell therapy for lung cancer: is it a better choice in the future? - Liu, Fengqin; Miao, Xia; Han, Lu; Song, Xiao (Frontiers in Oncology, 2024)
Lung cancer remains one of the leading causes of cancer-related mortality worldwide, necessitating the development of innovative therapeutic strategies. Chimeric Antigen Receptor (CAR) Natural Killer (NK) cell therapy represents a promising advancement in the field of oncology, offering a novel approach to target and eliminate tumor cells with high specificity and reduced risk of immune-related adverse effects. This paper reviews the mechanism, potential targets, and recent advances in CAR-NK cell therapy for lung cancer, including the design and engineering of CAR-NK cells, preclinical studies, and the outcomes of early-phase clinical trials.We highlight the unique advantages of using NK cells, such as their innate ability to recognize and kill cancer cells and their reduced potential for inducing graft-versus-host disease (GvHD) and cytokine release syndrome (CRS) compared to CAR-T cell therapies. Results from recent studies demonstrate significant antitumor activity in lung cancer models, with improved targeting and persistence of CAR-NK cells observed in vitro and in vivo. Finally, we discuss the challenges in optimizing CAR-NK cell therapies, including the potential resistance mechanisms. The paper concludes with an outlook on the future directions of CAR-NK cell research and its implications for lung cancer treatment, emphasizing the importance of continued innovation and collaboration in the field.